Advances in the application of food-derived exosomes as natural nanocarriers for the delivery of bioactive phenolic compounds - Yanhan Cui; Zhu Lin; Hongmin Zhen; Seid Mahdi Jafari; Chen Tan (Food Bioscience, 2026)

Efficacy of a non-recombinant NADC34-like PRRSV-2 vaccine candidate against a recombinant NADC34-like PRRSV-2 isolate - Ming Qiu; Shuai Li; Meng Cui; Shuai Yang; Xiaoyang Zhu; Yifan Meng; Yanhan Lin; Hong Lin; Zhe Sun; Yuan Wang; Sen Jiang; Wanglong Zheng; et al. (Veterinary Microbiology, 2025)

Co-encapsulation of bioactive compounds in liposomal delivery systems for synergistic effects - Xinghui Shen; Linyang He; Yanhan Cui; Zhu Lin; Seid Mahdi Jafari; Chen Tan (Food Bioscience, 2025)

Foodborne iron overload induces oxidative stress and causes mitochondrial damage in the liver of grass carp (Ctenopharyngodon idellus) - Xiaoman Huang; Yan Yang; Yanhan Bai; Shiyi Yang; Bing Chen; Linpeng Zhang; Lihan Liu; Junjie Tao; Chengming Tu; Li Lin; Zhendong Qin (Aquaculture, 2025)

Passive protection of chicken egg yolk immunoglobulin (IgY) against Streptococcus agalactiae infection in Nile tilapia (Oreochromis niloticus) - Linpeng Zhang; Yucong Hong; Kaihui Sun; Shuyan Zhao; Yanhan Bai; Shiyi Yang; Junjie Tao; Fei Shi; Fanbin Zhan; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Effects of feeding chicken egg yolk antibodies on intestinal cell apoptosis, oxidative stress and microbial flora of tilapia (Oreochromis niloticus) infected with Streptococcus agalactiae - Linpeng Zhang; Yanhan Bai; Junjie Tao; Shiyi Yang; Chengming Tu; Lihan Liu; Xiaoman Huang; Lin Li; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Exploration of the immune response of grass carp (Ctenopharyngodon idellus) erythrocytes during bacterial infection - Shiyi Yang; Yanhan Bai; Junjie Tao; Chengming Tu; Bing Chen; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Lin Li; Zhendong Qin (Fish & Shellfish Immunology, 2024)

FerrylHb induces inflammation and cell death in grass carp (Ctenopharyngodon idella) hepatocytes - Junjie Tao; Lihan Liu; Xiaoman Huang; Chenming Tu; Linpeng Zhang; Shiyi Yang; Yanhan Bai; Lin Li; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Immune response mechanisms underlying bacterial infection in Aquarana catesbeiana erythrocytes - Yanhan Bai; Lingqin Lu; Junjie Tao; Chengming Tu; Bing Chen; Shiyi Yang; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Li Lin; Zhendong Qin (Aquaculture, 2024)

Ranking the risk of antibiotic resistance genes by metagenomic and multifactorial analysis in hospital wastewater systems - Xinyi Shuai; Zhenchao Zhou; Lin Zhu; Chioma Achi; Zejun Lin; Zhe Liu; Xi Yu; Jinyu Zhou; Yanhan Lin; Hong Chen (Journal of Hazardous Materials, 2024)

The infection of Aeromonas hydrophila activated Multiple programmed cell death pathways in red blood cells of Clarias fuscus - Junjie Tao; Chengming Tu; Zizheng Xu; Yanhan Bai; Bing Chen; Shiyi Yang; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Bacteriophages: Vectors of or weapons against the transmission of antibiotic resistance genes in hospital wastewater systems? - Xinyi Shuai; Zhenchao Zhou; Xiaoliang Ba; Yanhan Lin; Zejun Lin; Zhe Liu; Xi Yu; Jinyu Zhou; Guangshu Zeng; Ziye Ge; Hong Chen (Water Research, 2024)

Identification of genomic-wide genetic links between cutaneous melanoma and obesity-related physical traits via cFDR - Shen Lin; Runnan Shen; Jingqian Huang; Yanhan Liu; Hongpeng Li; Qingfang Xu (Genes & Genomics, 2023)

The regulation mechanism of hematopoiesis during ischemic and hemolytic anemia in grass carp(Ctenopharyngodon idella) - Lixiang Wei; Yanhan Bai; Rishen Liang; Junyan Lin; Minxuan Yang; Ying Tang; Hong Chen; Minshan Yao; Yao Huang; Li Lin; Zhendong Qin (Aquaculture, 2023)

l-Arginine alleviates heat stress-induced intestinal epithelial barrier damage by promoting expression of tight junction proteins via the AMPK pathway - Zhaofei Xia; Liqing Huang; Peng Yin; Fenghua Liu; Yanhan Liu; Zhenbiao Zhang; Jiabao Lin; Wenshu Zou; Chunxiao Li (Molecular Biology Reports, 2019)
Heat stress (HS) and secondary restricted blood flow to the intestines cause dysfunction of the intestinal epithelial barrier. Tight junctions (TJs) are essential to maintain intestinal integrity. l -Arginine has beneficial effects on gut functions. However, the underlying mechanisms remain largely unknown. This study tested the hypothesis that l -arginine regulates the TJ network by activating AMP-activated protein kinase (AMPK) signaling, which in turn improves intestinal barrier functions under HS. IEC-6 cells and rat small intestines were used as experiment models of heat stress. AICAR and dorsomorphin were used to activate and inhibit the AMPK pathway, respectively. Cell proliferation, apoptosis, differential gene expression and KEGG pathway analysis, intestinal paracellular permeability, intestinal morphology, and expression of HSP and TJ proteins, and p-AMPK were determined. l -Arginine promoted cell proliferation and reduced apoptosis after heat exposure at an optimal concentration of 5 mmol. Transcriptome sequencing analysis revealed that differentially expressed genes associated with the HSP family and TJs were elevated by l -arginine. According to KEGG pathway analysis, l -arginine activated the AMPK signaling pathway. In vivo, intestinal damage resulted in obvious morphological changes as well as apoptosis with TUNEL and caspase-3 staining under HS and dorsomorphin treatments. Furthermore, HS and dorsomorphin increased the serum D-lactate concentration, diamine oxidase activity, and mRNA expression level of MLCK ( P < 0.05). In contrast, l -arginine and AICAR treatments reduced intestinal injury, maintained intestinal permeability, and increased the villus/crypt ratio under hyperthermia. l -Arginine had the same effect as AICAR both in vitro and in vivo, namely increasing p-AMPK protein expression. l -Arginine and AICAR also upregulated the mRNA expression level of HSP70 and HSP90, and downregulated mRNA expression of MLCK ( P < 0.05). The protein expression levels of TJ proteins ZO-1 and claudin-1 were suppressed by heat stroke and dorsomorphin, but enhanced by l -arginine and AICAR. Our findings indicate that activation of AMPK signaling by l -arginine is associated with improved intestinal mucosal barrier functions by enhancing the expression of TJs in rat small intestines and IEC-6 cells during HS.